Emerging Role of Eosinophils in Resolution of Arthritis - Qin, Yi; Jin, Hui-Zhi; Li, Yu-Jing; Chen, Zhu (Frontiers in Immunology, 2021)
Eosinophils are a minor component of circulating granulocytes which are classically viewed as end stage effector cells in host defense against helminth infection and promoting allergic responses. However, a growing body of evidence has emerged that eosinophils are versatile leukocytes acting as an orchestrator in the resolution of inflammation. Rheumatoid arthritis (RA) is the most common chronic inflammatory disease characterized by persistent synovitis that hardly resolves spontaneously. Noteworthy, a specific population of eosinophils, that is regulatory eosinophils (rEos), was identified in the synovium of RA patients, especially in disease remission. Mechanistically, the rEos in the synovium display a unique pro-resolving signature which is distinct from their counterpart in the lung. Herein, we summarize the latest understanding of eosinophils and their emerging role in promoting resolution of arthritis. These knowledge are crucial to design new approaches to rebalance immune homeostasis in RA, considering current therapy are centered on inhibiting pro-inflammatory cytokines and mediators rather than fostering resolution of inflammation.